Welding Training for Student with Special Needs at SLB Pelita Hati Pekanbaru - Mustaza Maa; Roni Novison; Made Rahmawaty (Politeknik Caltex Riau, 2024)
Welding training for students is part of a Community Service initiatie led by lecturers form Industrial Technology Departemen , Politeknik Caltex Riau., in line with the Tri Dharma of Higher Education. The goal of this training is to equip SLB Pelita Hati students with knowledge and skills in welding, promoting their independence. The training covers topics such as an introduction to SMAW welding,, welding fundamentals, equipment, safety practices, applications in product creation. The training took place over two days at SLB Pelita Hati. Following the training, ongoing guidance was provided, particularly fosuces on the products the students aimed to create. The students successfully produced tables, chairs, and shoe racks for their own use. As a result of this training, SLB Pelita Hati students are now able to independently manufacture table, chair and shoe racks products, fortering their self-sufficiency in community life